PEMBERDAYAAN MASYARAKAT DESA DAHOR MELALUI INOVASI PUPUK ORGANIK CAIR (POC) UNTUK MENDUKUNG SDGs DAN PENGUATAN EKONOMI MERAH PUTIH - Ulva Badi' Rohmawati; Khurul Anam (Universitas Mataram, 2025)
Dahor Village possesses significant potential in biological resources; however, these have not been optimally utilized to support community welfare. The excessive use of chemical fertilizers has also had a negative impact on the environment and soil fertility. Limited access to quality fertilizers and a lack of skills in organic waste processing hinder agricultural productivity. The innovation of liquid organic fertilizer (LOF) made from local raw materials emerges as an appropriate solution to these challenges. This activity aims to empower the community of Dahor Village through training and assistance in LOF production to enhance economic self-reliance and support the achievement of the Sustainable Development Goals (SDGs). The method employed involved a participatory approach through outreach, technical training, hands-on LOF production, and evaluation of activity outcomes. The participants included farmer groups, housewives, and village youth. The results showed a high level of enthusiasm from the community, demonstrated by increased knowledge and skills in producing and applying LOF. The community began reducing the use of chemical fertilizers and switching to more environmentally friendly LOF. In addition to improving crop yields, LOF is now marketed locally as a flagship village product. Household incomes increased, and awareness of organic waste management grew significantly. This initiative also strengthened community collaboration and supported a local economy based on green innovation. In conclusion, LOF innovation has proven effective in promoting sustainable agricultural practices, strengthening the village economy, and aligning with the spirit of the Merah Putih Economy and the achievement of the SDGs